2007
DOI: 10.1016/j.bmc.2007.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Darunavir, a conceptually new HIV-1 protease inhibitor for the treatment of drug-resistant HIV

Abstract: Our structure-based design strategies which specifically target the HIV-1 protease backbone, resulted in a number of exceedingly potent nonpeptidyl inhibitors. One of these inhibitors, darunavir (TMC114), contains a privileged, structure-based designed high-affinity P2 ligand, 3(R),3a(S),6a (R)-bis-tetrahydrofuranylurethane (bis-THF). Darunavir has recently been approved for the treatment of HIV/AIDS patients harboring multidrug-resistant HIV-1 variants that do not respond to previously existing HAART regimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
188
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(193 citation statements)
references
References 32 publications
(3 reference statements)
4
188
0
1
Order By: Relevance
“…Proposed method is validated as per ICH guideline for Analytical Procedures 6 . Recent studies suggested that protease inhibitors like Darunavir, Ritonavir, Nelfinavir showed no evidence of antagonism when used with TMC114 7,8 . Literature survey reveals that there are reports describing the determination of Darunavir in Plasma using liquid chromatography coupled with Tandem Mass Spectroscopy 9 , few HPTLC method for determination of Darunavir in rat plasma and in tablet dosage form its application to pharmacokinetic studies 10,11 , infrared spectroscopy method for determination of Darunavir in tablets 12 , and few RP-HPLC and Spectrophotometric methods 13,14 .…”
Section: Darunavir Is Chemically (3r3as6ar)-hexahydrofuro[23-b]furmentioning
confidence: 99%
“…Proposed method is validated as per ICH guideline for Analytical Procedures 6 . Recent studies suggested that protease inhibitors like Darunavir, Ritonavir, Nelfinavir showed no evidence of antagonism when used with TMC114 7,8 . Literature survey reveals that there are reports describing the determination of Darunavir in Plasma using liquid chromatography coupled with Tandem Mass Spectroscopy 9 , few HPTLC method for determination of Darunavir in rat plasma and in tablet dosage form its application to pharmacokinetic studies 10,11 , infrared spectroscopy method for determination of Darunavir in tablets 12 , and few RP-HPLC and Spectrophotometric methods 13,14 .…”
Section: Darunavir Is Chemically (3r3as6ar)-hexahydrofuro[23-b]furmentioning
confidence: 99%
“…The future management of HIV/AIDS should rely upon the development of therapies that are less toxic and more effective in combating drugresistance. 1 In this context, the Darunavir have enjoyed a surge in popularity as a new generation of PIs bearing a structure-based designed bis-THF ligand that effectively fills in the hydrophobic pocket and maximizes hydrogen bonding interactions with the backbone atoms of the S2-site.…”
Section: -3mentioning
confidence: 99%
“…Several reviews describe the benefits of applying continuous-flow methods in organic synthesis, including better mixing, efficient mass and heat transfer, and the ability to readily scale-up a given flow process by applying numbering-up or scaling-out principles [1,2]. A particularly challenging area in flow chemistry is the synthesis of active pharmaceutical ingredients (APIs), which typically involves a significant number of synthetic steps, and is therefore clearly a rather complex operation [6]. Recently, our group demonstrated the advantages of continuous-flow chemistry in the synthesis of important HIV protease inhibitor building blocks, such as Atazanavir.…”
Section: Introductionmentioning
confidence: 99%
“…Its high potency allows its use as a rescue drug in patients where standard treatment fails. Structurally, Darunavir (1) bears a (3R,3aS,6aR)-hexahydrofuro [2,3-b] furan-3-ol core which fills the hydrophobic pocket of the HIV protease and maximizes hydrogen bonding interactions with the backbone atoms of the active site [6].…”
Section: Introductionmentioning
confidence: 99%